2022
DOI: 10.1002/ett.4534
|View full text |Cite
|
Sign up to set email alerts
|

ONOS Flood Defender: An Intelligent Approach to Mitigate DDoS Attack in SDN

Abstract: Software-Defined Networking (SDN) has made its place in the networks as new technology. SDN's programmable behavior enables it to change behavior on the fly, provides instructions for the task's automatic performance, dynamic scaling, and service integration. These advantages have made SDN necessary in networks. However, SDN suffers from the threat of DDoS attack. We have developed an approach to mitigate these threats by creating an ONOS Flood Defender Application (OFD App). This app effectively detects DDoS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…Attackers generally use the same IP protocol to attack the network, which will reduce the randomness of the network IP protocol. [26]. Therefore, the entropy value of IP protocols is also an important indicator.…”
Section: Relevant Features Of the Precise Detection Methodsmentioning
confidence: 99%
“…Attackers generally use the same IP protocol to attack the network, which will reduce the randomness of the network IP protocol. [26]. Therefore, the entropy value of IP protocols is also an important indicator.…”
Section: Relevant Features Of the Precise Detection Methodsmentioning
confidence: 99%
“…Authors of Reference [40] developed a method for addressing DDoS attacks in SDN networks by setting the ONOS Flood Defender Application, which employs supervised and ensemble machine learning techniques such as MLP, SVM, KNN, XGBoost, AdaBoost, RF, Bagging classifier, and Gradient Boosting (GB). This method uses the correlation matrix and DT technique to handle the feature selection process and K ‐fold cross‐validation for optimization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these approaches, AEs have demonstrated promise in identifying anomalies in network traffic patterns, 34 while XGBoost is a machine learning algorithm that performs well in classification tasks related to the DDoS area. 37,40 Additionally, optimizing feature selection and hyperparameters can further enhance the performance of machine learning algorithms. Feature selection entails identifying the most relevant features in the dataset, while hyperparameter tuning involves selecting the best combination of hyperparameters for the model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naziya et al 37 suggested the model called ONOS flood defender model to mitigate a DDoS attack in SDN. The machine learning approaches in the ensemble model in this application detect the DDoS attack more efficiently.…”
Section: Related Workmentioning
confidence: 99%